The role of flourishing in the STEM trajectories of emerging adults - Hammerness, Karen; Chaffee, Rachel; Bjorklund, Peter; Hinton, Priya-Syrina Li; Daly, Alan J.; MacPherson, Anna; Gupta, Preeti; Adams, Jennifer D.; Braverman, Coral; Francis, Jahneal; Lagodich, Lucie; Wu, Lois; et al. (Frontiers in Education, 2024)
We focus on the use of flourishing as a new measure in studies of pathways in STEM (science, technology, engineering, and mathematical) fields. While the concept of flourishing is promising, the concept may need careful interrogation to ensure it takes structural and personal (cultural, religious, socioeconomic, and racial) differences into account. Our longitudinal study explores emerging adult’s educational and career pathways with careful attention to structural inequities, enabling us to productively explore the concept of flourishing in a larger systemic context. Drawing from a set of qualitative interviews with our participants, we explore the ways that our sample of emerging adults (N=30), predominantly people of color, define and discuss flourishing. The concept resonated with our diverse participants, and a substantial number did report flourishing. But despite the regularity with which the participants described experiencing racism and microaggressions, they did not often mention those harmful experiences when discussing flourishing. We caution that flourishing data on its own may provide an overly rosy image of the pathways and development, especially of young people of color. Our data suggest that it may be especially important to examine flourishing in context with other measures that can flesh out a fuller picture of well-being, especially in relation to race, racism, sexism, or any other experiences related to personal identities. In particular, instruments should be carefully designed to ensure–especially for emerging adults–that all aspects of their lives and identities can be fully understood.